Comparative metagenomic analysis of microbial community compositions and functions in cage aquaculture and its nearby non-aquaculture environments - Liu, Zetian; Wang, Pandeng; Li, Jialing; Luo, Xiaoqing; Zhang, Ya; Huang, Xiaohong; Zhang, Xin; Li, Wenjun; Qin, Qiwei (Frontiers in Microbiology, 2024)
In the context of burgeoning global aquaculture, its environmental repercussions, particularly in marine ecosystems, have gained significant attentions. Cage aquaculture, a prominent method, has been observed to significantly influence marine environments by discharging substantial amounts of organic materials and pollutants. It is also one of the important reasons for water eutrophication. This study investigated the impacts of cage aquaculture on microbial diversity and functional potential using metagenomics. Specifically, a comparison was made of the physicochemical indicators and microbial diversity between three grouper aquaculture cage nets in Lingshui Xincun Port and three nearby non-aquaculture area surface waters. We found that compared to nonaquaculture areas, the eutrophication indicators in aquaculture environments significantly increased, and the abundances of Vibrio and Pseudoalteromonas in aquaculture environments significantly rose. Additionally, microbial functional genes related to carbon, nitrogen, and sulfur metabolisms were also found to be significantly affected by aquaculture activities. The correlation analysis between microbial populations and environmental factors revealed that the abundances of most microbial taxa showed positive correlations with dissolved inorganic nitrogen, soluble reactive phosphorus, NH4 + , and negative correlations with dissolved oxygen. Overall, this study elucidated the significant impacts of aquaculture-induced eutrophication on the diversity and functions of planktonic bacterial communities.